2021
DOI: 10.3389/fnagi.2021.768948
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Human Induced Pluripotent Stem Cells-Derived In vitro Models for the Future Study of Sex Differences in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is an aging-dependent neurodegenerative disease that impairs cognitive function. Although the main pathologies of AD are the aggregation of amyloid-beta (Aβ) and phosphorylated Tau protein, the mechanisms that lead to these pathologies and their effects are believed to be heterogeneous among patients. Many epidemiological studies have suggested that sex is involved in disease prevalence and progression. The reduction of sex hormones contributes to the pathogenesis of AD, especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…7 b). ELISA measurement of Aβ 1-42 and Aβ 1-40 confirmed the increased ratio of Aβ 1-42 /Aβ 1-40 in the APP V717L co-culture model compared to the control co-culture model as previously reported [ 17 , 28 ] (Fig. 7 c).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…7 b). ELISA measurement of Aβ 1-42 and Aβ 1-40 confirmed the increased ratio of Aβ 1-42 /Aβ 1-40 in the APP V717L co-culture model compared to the control co-culture model as previously reported [ 17 , 28 ] (Fig. 7 c).…”
Section: Resultssupporting
confidence: 87%
“…To examine if our co-culture model can recapitulate the AD-like phenotypes, we co-cultured neurons and astrocytes derived from iPSCs bearing the familial AD (fAD) mutation ( APP V717L ) [ 17 , 28 ]. The iPSC line (APP2E26 line) from a female donor harboring the mutation of familial AD ( APP V717L ) were obtained [ 17 ], and we confirmed a single nucleotide substitution (G > C) at APP Exon 17 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical trials of estrogen replacement therapy to prevent AD development in postmenopausal women resulted in various conclusions. While some clinical studies have suggested the positive effects of E2 in preventing the onset of AD and improving symptoms in patients, some studies concluded that E2 treatment has no significant effects on AD protection (Reviewed in [ 29 ]). To conclude the E2 effects in clinical studies, we conducted a systematic review and meta-analysis of 15 articles related to Alzheimer's disease onset and estrogen replacement therapy, which includes a total of 483,511 patients ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, iPS cells can overcome the limitation of species differences among experimental animals and human, and facilitate studies on single cells or the cell-cell interactions. 98,99 Some groups have already demonstrated the roles of E2 100 and testosterone 101 using iPS cells derived from healthy subjects and autism patients, respectively. Such studies involved the analysis of iPS-derived neurons; thus, the effects of sex hormones on iPS-derived glial cells and neuroinflammation could be analyzed in future studies.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The analysis of sex hormones using induced pluripotent stem (iPS) cells derived from AD patients is useful as a bridge between AD model mice and humans. For example, iPS cells can overcome the limitation of species differences among experimental animals and human, and facilitate studies on single cells or the cell–cell interactions 98,99 . Some groups have already demonstrated the roles of E2 100 and testosterone 101 using iPS cells derived from healthy subjects and autism patients, respectively.…”
Section: Conclusion and Perspectivementioning
confidence: 99%